Penanganan inversio uteri: sebuah tinjauan pustaka - Endang Sri Widiyanti; I Gede Mega Putra (DiscoverSys Inc., 2022)
Acute uterine inversion is a rare but life-threatening emergency in the field of obstetrics. The main signs and symptoms of acute uterine inversion are bleeding and shock. The accuracy and speed of diagnosis and case management will reduce morbidity and mortality due to uterine inversion. This literature review is expected to increase our knowledge as practitioners in dealing with uterine inversion cases. In principle, there are two goals for the treatment of acute uterine inversion, namely repositioning the uterus and treating the shock that occurs. The success of uterine inversion repositioning is highly dependent on the speed of early detection. The longer the uterus is inverted, the more difficult it will be to reposition it. There are several non-surgical techniques for repositioning the uterus, including: Johnson maneuver, Henderson and Alles maneuver, use of tocolytics, and repositioning with hydrostatic pressure. Surgical procedures can be performed abdominally, namely the Huntington's Procedure, with abdominal repositioning laparotomy and the Haultain's Procedure, with abdominal cervical repositioning-repositioning laparotomy. Kejadian inversio uteri akut merupakan kegawatdaruratan di bidang Obstetri yang jarang terjadi namun mengancam nyawa. Tanda dan gejala utama inversio uteri akut adalah perdarahan dan syok. Ketepatan dan kecepatan diagnosa dan penanganan kasus akan mengurangi morbiditas dan mortalitas akibat inversio uteri. Tinjauan pustaka ini diharapkan dapat menambah pengetahuan kita sebagai praktisi dalam menangani kasus inversio uteri. Pada prinsipnya ada dua tujuan penanganan inversio uteri akut, yaitu reposisi uterus dan penanganan syok yang terjadi. Keberhasilan reposisi inversio uteri sangat tergantung pada kecepatan deteksi dini. Semakin lama uterus terinversi akan semakin sulit melakukan reposisi. Terdapat beberapa teknik non-bedah untuk reposisi inversio uteri, antara lain: manuver Johnson, manuver Henderson dan Alles, penggunaan tokolitik, dan reposisi dengan tekanan hidrostatik. Prosedur pembedahan dapat dilakukan melalui abdominal, yaitu Prosedur Huntington, dengan laparotomi-reposisi melalui abdominal dan Prosedur Haultain, dengan laparotomi- insisi cincin servikalis-reposisi melalui abdominal.